PERBANDINGAN HUKUM JUAL BELI TANAH DI INDONESIA DAN LAOS: Comparison Of Land Sale And Purchase Laws In Indonesian And Laos - Putri, Febby Permata; Keumala, Dinda (AMICUS CURIAE, 2024)
Differences in land buying and selling laws in Indonesia and Laos are due to different conceptions adopted by each country. The formulation of the problem in this study is how are the similarities and differences in the laws of buying and selling land in Indonesia and Laos. The conclusion of this study is the similarity, regarding the arrangement of land rights, where foreign nationals cannot buy land to be controlled permanently; its land registration system; the function of the deed of sale and purchase of land; and land sale and purchase registration function. In addition to similarities, there are also differences regarding the regulations/legal basis for buying and selling land; definition of buying and selling land; implementation of land sale and purchase; making deed of sale and purchase of land; land sale and purchase registration; or at the time of the transfer of rights.